Intervensi Variabel Gaya Hidup pada Layanan Grab Food dan Diskon Harga dalam Mempengaruhi Pola Konsumtif Masyarakat - Ali Mauludi AC; Adhimas Priyoga; Budi Kolistiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of GrabFood services and food price discounts on the consumption patterns of the Tulungagung community, with lifestyle as an intervening variable. The phenomenon of increasing use of food delivery applications such as GrabFood and the attraction of price discounts have changed people's shopping habits. Tulungagung, as one of the areas that also feels the impact of digitalization, shows a shift in consumption patterns. This study aims to analyze the influence of GrabFood services and food price discounts on the consumption patterns of the Tulungagung community, with lifestyle as an intervening variable. The phenomenon of increasing use of food delivery applications such as GrabFood and the attraction of price discounts have changed people's shopping habits. Tulungagung, as one of the areas that also feels the impact of digitalization, shows a shift in consumption patterns. This study aims to analyze the influence of GrabFood services and food price discounts on the consumption patterns of the Tulungagung community, with lifestyle as an intervening variable. The phenomenon of increasing use of food delivery applications such as GrabFood and the attraction of price discounts have changed people's shopping habits. Tulungagung, as one of the areas that also feels the impact of digitalization, shows a shift in consumption patterns Keywords: Grab Food Service, Price Discount, Lifestyle, Consumption Pattern